2022
DOI: 10.1039/d2fo00919f
|View full text |Cite
|
Sign up to set email alerts
|

A comparative study between olive oil and corn oil on oxidative metabolism

Abstract: Fats are an important part of diet, but not all lipids have the same structure and chemical properties.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
1
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(3 citation statements)
references
References 78 publications
0
1
0
Order By: Relevance
“…Meantime, vegetable oils like coconut oil possess 90% of medium chain saturated fats (like, lauric acid), which differ from animal saturated fats; they are easily absorbed in small intestine and do not undergo degradation or re-esterification [ 25 ]. Olive oil and corn oil possess a lipid source respectively of monounsaturated and polyunsaturated fatty acids [ 26 ].…”
Section: Discussionmentioning
confidence: 99%
“…Meantime, vegetable oils like coconut oil possess 90% of medium chain saturated fats (like, lauric acid), which differ from animal saturated fats; they are easily absorbed in small intestine and do not undergo degradation or re-esterification [ 25 ]. Olive oil and corn oil possess a lipid source respectively of monounsaturated and polyunsaturated fatty acids [ 26 ].…”
Section: Discussionmentioning
confidence: 99%
“…Epidemiological studies have demonstrated that olive oil is rich in antioxidants, which can help prevent oxidative stress, which contributes to the development of diseases such as CVD, cancer, and neurodegenerative diseases [57,74,75]. Olive oil phenols are potent antioxidants because of their capacity to scavenge ROS produced by oxidative stress and stimulate the activity and synthesis of antioxidant enzymes.…”
Section: Olive Oil and The Animal Studies On Its Antioxidant Propertiesmentioning
confidence: 99%
“…In other words, it does not exert undesirable effects on the body, but it may mask the toxic effects of the compound. Corn oil is also a vegetable oil, and comparisons with olive oil have frequently been reported (Gao et al, 2019;Drehmer et al, 2022). Corn oil does not exhibit antioxidant properties and has not been shown to differ from olive oil as a subcutaneously administered vehicle (Wu et al, 1994).…”
Section: Introductionmentioning
confidence: 99%